2002
DOI: 10.1103/physrevb.66.035313
|View full text |Cite
|
Sign up to set email alerts
|

Conductance of one-dimensional quantum wires

Abstract: We discuss the conductance of quantum wires (QW) in terms of the Tomonaga-Luttinger liquid (TLL) theory. We use explicitly the charge fractionalization scheme which results from the chiral symmetry of the model. We suggest that results of the standard two-terminal (2T) conductance measurement depend on the coupling of TLL with the reservoirs and can be interpreted as different boundary conditions at the interfaces. We propose a three-terminal (3T) geometry in which the third contact is connected weakly to the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 44 publications
0
44
0
Order By: Relevance
“…The interaction between counterpropagating channels generates small amount of dragged charges reverse-travelling in the subsidiary channels (charge fractionalization), as illustrated by coupled wave packets in Fig. 1(a) [24,32,33].…”
Section: A Plasmon Excitation In Edge Channelsmentioning
confidence: 99%
“…The interaction between counterpropagating channels generates small amount of dragged charges reverse-travelling in the subsidiary channels (charge fractionalization), as illustrated by coupled wave packets in Fig. 1(a) [24,32,33].…”
Section: A Plasmon Excitation In Edge Channelsmentioning
confidence: 99%
“…Moreover, a single TLL can have inhomogeneities: e.g., a contact between an interacting TLL and a Fermi-liquid lead, a key ingredient of most transport measurements, is often studied as an inhomogeneous TLL wire smoothly interpolating between interacting (TLL) and noninteracting (Fermi-liquid) regions or as a two-wire junction with the Luttinger parameter abruptly changing at the junction. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] A junction of three quantum wires with different Luttinger parameters has been studied in the weak coupling regime. 21,[57][58][59] The experimental importance of junctions of TLL wires with generally unequal Luttinger parameters motivates an in-depth study of their properties, which is the main objective of the present paper.…”
mentioning
confidence: 99%
“…When an electron is injected in the bulk of a quantum wire at a given Fermi point, say, −k F , this gives rise to two counterpropagating pieces which carry charge f e and (1 − f )e, respectively, where f = (1 + g)/2 [8,9,10,11,12]. We have shown that the ratio between the asymmetry A S = (I L − I R )/I S and the two-terminal conductance G 2 in the almost equilibrium regime, where the applied bias voltages are small compared to k B T /e, allows to construct a novel dimensionless ratio reflecting the charge fractionalization phenomenon,…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, we introduce the chiral fields of nonchiral Luttinger liquids [1,8,9,11,15,27]. It is indeed convenient to distinguish the charge excitations propagating to the left (−) from the charge excitations propagating to the right (+).…”
Section: Chiral Basismentioning
confidence: 99%
See 1 more Smart Citation